OPTIMALISASI PENGGUNAAN ELSE-U UNTUK MATEMATIKA KONSEPTUAL - HARINI, LUH PUTU IDA; SARI, KARTIKA; KENCANA, EKA N. (E-Jurnal Matematika; Vol 7 No 3 (2018), 2018)
Udayana University is one of the universities that have developed an e-learning system that is coupled with the IMISSU (Integrated Management Information System of the Udayana) system and is known as the ELSE-U (E-Learning Smart and Elegant of Udayana). This system was built with the aim of accommodating online lectures. But in reality there are still many lecturers, especially in the Mathematics Department who have not utilized the learning media. Many reasons related to the media have not been utilized. In this study, a material development strategy and learning using ELSE-U will be initiated for conceptual mathematics material in order to obtain optimal benefits. In addition, the measurement of the level of acceptance and use of the utilization of ELSE-U in learning is carried out using the Technology Acceptance Model (TAM) method. The results showed that the internal and external factors of students did not affect the perceived ease of use in the use of ELSE-U, organizational factors (study programs, faculties, and universities) had a significant effect on perceived usefulness and perceived ease of use in the use of ELSE-U, while student behavior in addressing the use of ELSE-U has a significant effect on students' intention to use it.